Effectiveness of an anti-algal compound in eliminating an aquatic unicellular harmful algal Phaeocystis globosa - Huajun eZhang; Huajun eZhang; Yun ePeng; Su eZhang; Guanjing eCai; Yi eLi; Xujun eYang; Ke eYang; Zhangran eChen; Jun eZhang; Hui eWang; Wei eZheng; et al. (Frontiers in Microbiology, 2016)
Phaeocystis globosa blooms can have negative effects on higher trophic levels in the marine ecosystem and consequently influence human activities. Strain KA22, identified as the bacterium Hahella, was isolated from coastal surface water and used to control P. globosa growth. A methanol extract from the bacteral cells showed strong algicidal activity. After purification, the compound showed a similar structure to prodigiosin when identified with Q-Exactive Orbitrap MS and nuclear magnetic resonance spectra. The compound showed algicidal activity against P. globosa with a 50% Lethal Dose (LD50) of 2.24 μg/mL. The prodigiosin was stable under heat and acid environment, and it could be degraded under alkaline environment and natural light condition. The growth rates of strain KA22 was fast in 2216E medium and the content of prodigiosin in this medium was more than 70 μg/mL after 16 h incubation. The compound showed particularly strong algicidal activity against Prorocentrum donghaiense, P. globosa and Heterosigma akashiwo, but having little effect on three other phytoplankton species tested. The results of our research could increase our knowledge on harmful algal bloom control compound and lead to further study on the mechanisms of the lysis effect on harmful algae.